Gender, Stress and Smoking Behavior on Young Adults in Banda Aceh - Novriana, Hasmelia; Faradina, Syarifah; Afriani, Afriani (SCAD Independent, 2021)
Young adult is a period of adaptation from adolescence to adulthood. The young adult is vulnerable to the onset of stress due to various demands and problems at hand. Stress is often associated with harmful behaviour one being smoking. Not only men but women are now becoming smokers too. The purpose of this study is to determine the relationship between gender, stress, and smoking behaviours in young adults in Banda Aceh. This research used the correlation research design. Incidental sampling technique was used with a total sample of 105 people (57 male smokers and 48 female smokers). Data was collected using an adapted version of the Depression Anxiety Stress Scale (DASS 42). Hypothesis test using the Spearman correlation test technique showed a significance of r = 0.37 (p) 0.00 (<0.05) on the relationship between gender and stress which means that women have higher stress than men. Results also showed there is a relationship between gender and smoking behaviour with a significance of r = -0.42 (p) 0.00 (>0.05), which means that men have a higher level of cigarette consumption than women.